1985
DOI: 10.5109/2481
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Proctotrupoid Wasps in Korea for Control of the Pine Needle Gall Midge, Thecodiplosis Ja Ponensis (Diptera, Cecidomyiidae)

Abstract: The pine needle gall midge is the most injurious pest of Pinus densifora and P. thwzbergii in Korea. In general, pine needle gall midge damage reaches a maximal level about 7 years following invasion by the midge, and parasite populations increase a few years thereafter. Four species of Platygastridae that parasitize the midge have been found in Korea, and their parasitization percentages are on the increase. Three of the parasites, P. matsutama, I. hockpari, and I. seoulis are effective natural enemies of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In recent years, T. japonensis have caused serious damage to P. thunbergii in Shandong, China. In South Korea, T. japonensis have been reported for nearly 100 years and have caused serious ecological and economic losses [ 9 , 10 ]. Inoculation tests showed that T. japonensis could infest a variety of pine trees, including P. massoniana , P. resinosa , P. thunbergii , Pinus sylvestris , Pinus mugo , Pinus luchuensis , Pinus tabulaeformis , Pinus radiata , Pinus coulteri , Pinus nigra , P. densiflora , Pinus taiwanensis and Pinus insularis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, T. japonensis have caused serious damage to P. thunbergii in Shandong, China. In South Korea, T. japonensis have been reported for nearly 100 years and have caused serious ecological and economic losses [ 9 , 10 ]. Inoculation tests showed that T. japonensis could infest a variety of pine trees, including P. massoniana , P. resinosa , P. thunbergii , Pinus sylvestris , Pinus mugo , Pinus luchuensis , Pinus tabulaeformis , Pinus radiata , Pinus coulteri , Pinus nigra , P. densiflora , Pinus taiwanensis and Pinus insularis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…and Pinus tabuliformis Carriere [ 8 ]. It is considered the most harmful pest to pines in South Korea, causing great damage to the South Korean ecological environment and economic development [ 9 , 10 ]. In Japan, T. japonensis could attack Pinus massonian Lambert [ 11 ].…”
Section: Introductionmentioning
confidence: 99%